2017
DOI: 10.1007/s10787-017-0359-7
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide, fluticasone propionate, and azithromycin do not modulate the membrane vesicle release by THP-1 macrophages and respiratory pathogens during macrophage infection

Abstract: Patients with more severe chronic obstructive pulmonary disease frequently experience exacerbations and it is estimated that up to 50% of these exacerbations are associated with bacterial infections. The mainstay treatment for these infection-related exacerbations constitutes the administration of glucocorticoids, alone or in combination with antibiotics. A recent line of evidence demonstrates that many hormones including the steroid beclomethasone can also directly affect bacterial growth, virulence, and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Only a limited number of studies have been allocated to the effect of these groups of antibiotics on changing membrane vesiculation patterns. The available results showed that they exert neither a significant inducing effect on membrane vesicle production nor on the level of virulence factors carried by membrane vesicles ( Bauwens et al, 2017 ; Volgers et al, 2017 ; Yun et al, 2018 ). In contrast to aminoglycosides, these groups of antibiotics do not directly affect membranes, and do not disrupt membrane stability.…”
Section: Antibioticsmentioning
confidence: 97%
“…Only a limited number of studies have been allocated to the effect of these groups of antibiotics on changing membrane vesiculation patterns. The available results showed that they exert neither a significant inducing effect on membrane vesicle production nor on the level of virulence factors carried by membrane vesicles ( Bauwens et al, 2017 ; Volgers et al, 2017 ; Yun et al, 2018 ). In contrast to aminoglycosides, these groups of antibiotics do not directly affect membranes, and do not disrupt membrane stability.…”
Section: Antibioticsmentioning
confidence: 97%
“…Amelioration of systemic inflammatory response syndrome (SIRS) induced by OMV was observed through the administration of salbutamol and nortriptyline, which exhibited inhibitory effects on the release of IL-6 and tumor TNF from macrophages ( 161 ). The suppression of proinflammatory responses induced by EVs obtained from various bacterial species has been observed with the administration of budesonide, N-acetyl-L-cysteine, and fluticasone ( 162 , 163 ). Moreover, it has been demonstrated that ethyl pyruvate possesses the capability to impede various signaling pathways involved in the immune responses triggered by LPS and Escherichia coli OMV.…”
Section: Clinical Potential Of Bevs In Sepsismentioning
confidence: 99%
“…Treatment of 0.1 μM 27 and 28 decreased TNF-α secretion by macrophages by approximately 84 and 83%, respectively in response to M. catarrhiae EVs. However, neither the release of EVs nor bacterial growth were affected ( Volgers et al, 2017b ). These findings suggest that 27 and 28 may have a positive effect on bacterial EV-induced inflammation, despite the observation that EV release and bacterial growth remained unaltered.…”
Section: Inhibitors Of Bacterial Extracellular Vesiclesmentioning
confidence: 99%